Exploring the Impact of Motivation, Leadership, and Education on Employee Performance: A Case Study of Energy and Mineral Resources Office in West Java, Indonesia - Rustandi, Rustandi (The International Journal of Business Review (The Jobs Review), 2023)
The purpose of this study was to determine and analyze motivation, leadership style and educational qualifications on employee performance. The research method used is a survey method with a quantitative research approach. The size of the research sample is 165 employees at the Department of Energy, Resources and Minerals of West Java Province. The technique of determining the sample is based on criteria. Data collection techniques using observation techniques and questionnaires. The data analysis technique uses path analysis using the SPSS application. The results of the study indicate that motivation, leadership style and educational qualifications have an effect either partially or simultaneously on employee performance